Development of a Bioproduct for Medicinal Use with Extracts of Zuccagnia-type Propolis - Salas, Ana Lilia; Zampini, Iris Catiana; Maldonado, Luis Maria; Isla, María Inés (Sage Publishing, 2022)
Propolis with a botanic origin in Zuccagnia punctata Cav. (Fabaceae), a plant species widely distributed in the Argentinean Monte region, was used to produce a standardized propolis extract by biological activity and chemical composition. In this paper the effect on microorganisms isolated from otitis was determined. The extract was active against different Staphylococcus strains with MIC and MBC values (75 and 150 μg DE/mL, 200 and 600 μg DE/mL, respectively) and with MIC values of 800 μg DE/mL against Proteus mirabilis. A pharmaceutical product, ear drops containing this extract as bioactive was developed. Stability of ear drops was evaluated for 6 months, and their biological activity, physical and phytochemical properties were preserved. Ear drops showed inhibitory activity on pro-inflammatory enzymes such as lipoxygenase (IC50 values 90 and 100 μg DE/mL), free radical-scavenging effect (SC50 values 23 and 30 μg DE/mL), antihelmintic (LC50 values 70 and 71 μg DE/mL), anti-candida (400 μg DE/mL) and antibacterial activity against Gram-positive bacteria (200 μg DE/mL) at zero time and during six month-storage, respectively. The content of two chalcones, chemical markers of Zuccagnia -type propolis was quantified and its level was maintained while stored at room temperature. Its toxicity was also assayed. Our results are interesting since the extract and ear drops of Zuccagnia -type propolis developed could be promising for use in alternative medicine or phytomedicine as antibacterial, anti-candida, antihelmintic, anti-inflammatory and antioxidant.